Cardiovascular Benefits With Favorable Renal, Amputation and Hypoglycemic Outcomes of SGLT-2 Inhibitors in Type 2 Diabetes From the Asian Perspective: A Population-Based Cohort Study and Systematic Review - Yang, Chun-Ting; Peng, Zi-Yang; Chen, Yi-Chi; Ou, Huang-Tz; Kuo, Shihchen (Frontiers in Endocrinology, 2022)
Objective: We assessed the effects of sodium glucose cotransporter-2 inhibitors (SGLT2is) versus dipeptidyl peptidase-4 inhibitors (DPP4is) in a large real-world Asian cohort with type 2 diabetes (T2D) and performed a systematic review with integrating the present study findings to provide up-to-date evidence from the Asian perspective. Methods: New users of SGLT2is or DPP4is were identified from Taiwan’s National Health Insurance Research Database and followed until 2018. Primary outcomes were hospitalization for heart failure (HHF) and three-point major adverse cardiovascular event (3P-MACE; including myocardial infarction [MI], stroke, or cardiovascular death). Other outcomes included all-cause death, chronic kidney disease (CKD), amputation, and hospitalized hypoglycemia. Subdistribution hazard models were employed to assess treatment-associated clinical outcomes. Results: 21,329 SGLT2i and DPP4i propensity-score-matched pairs were analyzed. SGLT2is versus DPP4is showed lower risks of HHF (hazard ratio [95% CI]: 0.52 [0.45-0.59]), 3P-MACE (0.62 [0.55-0.70]), MI (0.63 [0.50-0.79]), stroke (0.60 [0.51-0.70]), all-cause death (0.57 [0.49-0.67]), CKD (0.46 [0.43-0.50]), amputation (0.64 [0.42-0.98]), and hospitalized hypoglycemia (0.54 [0.45-0.64]). Our results were consistent with findings from a systematic review. Conclusion: Among Asian patients with T2D, SGLT2is versus DPP4is showed benefits for several clinical outcomes. More research is warranted to explore the heterogeneous treatment effects of SGLT2is and DPP4is by race/ethnicity.